(untitled) (Sociologisk Forskning, 1994)
Are public sector employees different? Sectorial and citizen attitudes in Swedish politics. This article raises the question whether it makes a difference for people’s attitudes towards the public sector to be employed by, or have their main income from, the private or the public sector. An analysis based on quantitative data from 1987 reveals that these dividing lines had no significant effect on the level of discontent with public activities such as health care, child care and eldercare, but proved to have a slight effect on attitudes to public institutions: state authorities, municipal authorities, the courts and parliament (Riksdagen). Public employees have somewhat greater confidence in these institutions. This effect remained more or less intact as tested against gender, education, age and occupation. The main conclusion however is that the impact of both type of employment and source of income is far too low to support the general idea that public/private affiliation in these respects is has any real importance for citizen attitudes in Sweden.